STUDI PENAMBAHAN GARDU SISIPAN TIPE TIANG UNTUK MENGATASI BEBAN LEBIH DI PT PLN (PERSERO) AREA CIANJUR RAYON MANDE - Giri Angga Setia; Hadi Umar Setiawan; Fauzia Haz; Een Taryana (Department of Electrical Engineering, UNJANI, 2022)
In the distribution system, blackouts caused by excessive loads cause losses for both consumers and electricity providers. Based on this, it is necessary to analyze the addition of distribution substations using an accurate methodology so that when applied it can be a solution to the need for electrical energi. Several stages of the method are determining the specifications of each component, calculating the optimal capacity of each component, measuring the voltage value contained in the panel and the primary part of the transformer at the hook-up substation, and simulating using ETAP software. The cantol substation was chosen because field studies have been carried out according to load requirements. The results of the calculation analysis show that with the addition of insertion substations, the total power becomes 100 kVA. The measured load at night is 77.7 kVA and during the day is 67.5 kVA. This indicates that the loading is in the allowable standard range below 80%. The voltage increased to 0.9828 per unit from the previous condition where there was a voltage drop of 11%. So that the load needs are met on demand.